Development of a novel method to grow mono-/few-layered MoS2 films and MoS2-graphene hybrid films for supercapacitor applications - Patil, Sagar; Harle, Arti S.; Sathaye, Shivaram; Patil, Kashinath (CrystEngComm, 2014)
The controlled synthesis of highly crystalline MoS2 atomic layers remains a challenge for practical applications of this emerging material. We demonstrate a facile method to synthesize crystalline mono-layered/few-layered MoS2 thin films at the liquid-liquid interface which can be suitably transferred to the substrates. The films are characterized by XRD for their crystal structure and by SEM and TEM for the morphology. MoS2 nanosheet-graphene nanosheet (MoS2-GNS) hybrid films have been developed by the application of layer-by-layer (LbL) techniques. Cyclic voltammetry and other electrochemical characterization techniques reveal that the hybrid film electrode shows a specific capacitance of 282 F g(-1) at a scan rate of 20 mV s(-1). The as-obtained hybrid electrode is robust and exhibits much improved cycle life (>1000), retaining over 93% of its initial capacitance as revealed by galvanostatic charge/discharge studies. The confirmation of better performance as a supercapacitor of the composite was studied by electrochemical impedance spectroscopy. These results indicate that the MoS2-GNS hybrid is a promising candidate for the electrode material in supercapacitor applications.

Detection of toxic metal ions Pb2+ in water using SiO2@Au core-shell nanostructures: A simple technique for water quality monitoring - Daware, Krishna; Kasture, Manasi; Kalubarme, Ramchandra; Shinde, Rakesh; Patil, Kashinath; Suzuki, Norihiro; Terashima, Chiaki; Gosavi, Suresh; Fujishim, Akira (Chemical Physics Letters, 2019)
The present paper demonstrates a development of simple, sensitive and selective optical probe for detection of Pb2+ ions in water using monodispersed silica-gold core-shell nanostructures (SiO2@Au NSs). Structural and elemental analysis confirms the phase purity of nanostructures. The SPR studies for SiO2 @Au NSs reveals, linear dynamic range for Pb2+ ions detection, in the concentration range of 100 ppb to 2 ppm, with detection limit of 100 ppb, which is 5 times higher than AuNPs. Cross sensitivity study confirm its selectivity towards Pb2+ ions over other metal ions. XPS analysis shows the interaction of Pb2+ ions with core-shell NPs.